Queering Childhood in Early Modern English Drama and Culture (Springer International Publishing, 2018)
This volume analyzes early modern cultural representations of children and childhood through the literature and drama of Shakespeare and his contemporaries. Contributors include leading international scholars of the English Renaissance whose essays consider asexuals and sodomites, roaring girls and schoolboys, precocious princes and raucous tomboys, boy actors and female apprentices, while discussing a broad array of topics, from animal studies to performance theory, from queer time to queer fat, from teaching strategies to casting choices, and from metamorphic sex changes to rape and cannibalism. The collection interrogates the cultural and historical contingencies of childhood in an effort to expose, theorize, historicize, and explicate the spectacular queerness of early modern dramatic depictions of children.